2020
DOI: 10.3390/ijerph17072252
|View full text |Cite
|
Sign up to set email alerts
|

Illness, Self-Rated Health and Access to Medical Care among Waste Pickers in Landfill Sites in Johannesburg, South Africa

Abstract: Waste pickers are exposed to various environmental health hazards, and self-rated health (SRH) could influence their medical care access. This study investigated the association between illness, clinic visits and SRH, and assessed if SRH can increase clinic visits. A cross-sectional study was conducted. SRH was defined as “very good”, “good”, “fair”, and “poor”. The illnesses were mental health, infectious, and chronic diseases. Medical care access included clinic visits in the previous 12 months. An ordinal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Also, waste pickers might have no or rare access to healthcare, as reported previously [31]. Furthermore, another study reported that 37% of the waste pickers did not consult a doctor in more than a year and 8% never measured their blood pressure including other health measurements [29].…”
Section: Discussionmentioning
confidence: 85%
“…Also, waste pickers might have no or rare access to healthcare, as reported previously [31]. Furthermore, another study reported that 37% of the waste pickers did not consult a doctor in more than a year and 8% never measured their blood pressure including other health measurements [29].…”
Section: Discussionmentioning
confidence: 85%
“…The waste pickers could be affected the worst given their level of poverty and stress, as they strive on daily basis to earn a living. Also, waste pickers might have no or rare access to healthcare, as reported previously [ 36 ]. Furthermore, another study reported that 37% of the waste pickers did not consult a doctor in more than a year and 8% never measured their blood pressure including other health measurements [ 34 ].…”
Section: Discussionmentioning
confidence: 89%
“…The study result found that, about 50% of the respondents rated their health condition as good. The finding can be related to a study which reported that 43% of the waste pickers surveyed in Johannesburg reported their health status as good [ 45 ]. Conversely, another study has reported more than 50% of the participants indicating their health condition as average [ 54 ].…”
Section: Discussionmentioning
confidence: 93%
“…Supported by the findings from the study are several related community health surveys that investigate a wide range of health complications related to environmental exposure to a landfill [ 44 ]. Increased occurrences of associated symptoms between waste picking and landfill such as illnesses, self-rated health, and clinic visit have been reported [ 45 ]. Reported study has also revealed the relationship between waste picking and mental health disorders [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation